Analisis Kecukupan Ruang Terbuka Hijau (RTH) Publik Dalam Menyerap Emisi Karbon Dioksida (CO2) Dari Kegiatan Transportasi Di Kecamatan Tampan Kota Pekanbaru - Hasdania, Annisa Meidiany; Sasmita, Aryo; Asmura, Jecky (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The green open space is one of an effort in order to handling of the increasing the greenhouse gas emission, because green open space has an ability to absorbing the CO2 emission. The purpose of this research is to find out the potential of absorption capacity of CO2 by the public’s green open space and to analyze the level of absorption of CO2 by green open space from transportation activity. The method in this research is calculate the value of CO2 emissions and counting the trees which has diameters more than 20 centimeter. The sufficiency of green open space was analyze and then compared the absorbing power of CO2 by trees with number of CO2 emissions that produced. Tampan district is produced the CO2 emissions from transportation which is high enough as much as 2.102.614.367 kilograms CO2/year. While the ability of CO2 absorption by the public’s green open space in Tampan district only 7.979.245,86 kilograms CO2/year. The result of analysis show that the public’s green open space in Tampan district that viewed from absorbing CO2 emissions of transportation is still not enough with percentage is only about 0,38%.Keywords: Green Open Space, Co2 Emissions, and Greenhouse Gas